The Implementation of Financial System Information toward The Function of Regional Financial Supervision on Regional Financial Management in Bungo Regency - Herawati Herawati (Journal on Education, 2023)
Utilization of today's technology is something that can't be avoided, because of the need for information very fast, and precisely becomes a necessity major in all aspects. One of the technologies that the most developed is the technology that web-based which is often referred to as Internet. This technology is already in use in various fields of business, government, health, education and so on. Internet technology that is now ingrained meat must be used optimally, the existence of technology is also expected to be the answer to generalize speed of service, an advancement if the government is starting to adopt the technology as the main infrastructure of public services. The application of SIMDA Financial application to the Bungo Regency Regional Financial is based on SIMDA elements such as adequate internet network access, basic infrastructure and applications, all infrastructure in the form of hardware, software, and brain ware is adequate as well as information management and processing organizations and electronic documents that are sufficient. So that, the SIMDA Financial Application has produced financial statement information and other financial information with excellent quality relevance, excellent accuracy, and very good timeliness as well.